If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(n + -8) = -3 + 6n Reorder the terms: -3(-8 + n) = -3 + 6n (-8 * -3 + n * -3) = -3 + 6n (24 + -3n) = -3 + 6n Solving 24 + -3n = -3 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 24 + -3n + -6n = -3 + 6n + -6n Combine like terms: -3n + -6n = -9n 24 + -9n = -3 + 6n + -6n Combine like terms: 6n + -6n = 0 24 + -9n = -3 + 0 24 + -9n = -3 Add '-24' to each side of the equation. 24 + -24 + -9n = -3 + -24 Combine like terms: 24 + -24 = 0 0 + -9n = -3 + -24 -9n = -3 + -24 Combine like terms: -3 + -24 = -27 -9n = -27 Divide each side by '-9'. n = 3 Simplifying n = 3
| 2y+12(4)+4(3)=16 | | 4.39N+3.44N=66.44 | | 5y^2-10x=4 | | =12L | | 3e^4x=26 | | 2n^0*3n= | | x(5-x)=-6 | | (3-7)= | | x-30=46 | | x^2+5x-2=3x+6 | | 4s^2+4s^2= | | f(z)=4x-1 | | 5*x^2=2x | | 5x*2=2x | | 10x-17=9x+5 | | 335-x=15 | | 4s^2+4s^2+6s-1+8-5s= | | 2+12=5+-9 | | 10x^2+40x-2000=0 | | 15a+3=33 | | 2x+12=5-9 | | 7(4p+2q+3r)= | | 29=5-3x | | 7x-(7+4x)= | | -8(u+5)=-64 | | 5x+5=2x-x+8 | | =(2n+14)-10 | | 4(3x+5)=34 | | 52x+13=3(x-12) | | -2(5y+-3)=56 | | 14-6-x= | | 3(x-3)-x=1 |